Skip to main content
Evaluate
Tick mark Image
Factor
Tick mark Image
Graph

Similar Problems from Web Search

Share

2x^{2}+6-13-7x
Combine -9x^{2} and 11x^{2} to get 2x^{2}.
2x^{2}-7-7x
Subtract 13 from 6 to get -7.
factor(2x^{2}+6-13-7x)
Combine -9x^{2} and 11x^{2} to get 2x^{2}.
factor(2x^{2}-7-7x)
Subtract 13 from 6 to get -7.
2x^{2}-7x-7=0
Quadratic polynomial can be factored using the transformation ax^{2}+bx+c=a\left(x-x_{1}\right)\left(x-x_{2}\right), where x_{1} and x_{2} are the solutions of the quadratic equation ax^{2}+bx+c=0.
x=\frac{-\left(-7\right)±\sqrt{\left(-7\right)^{2}-4\times 2\left(-7\right)}}{2\times 2}
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
x=\frac{-\left(-7\right)±\sqrt{49-4\times 2\left(-7\right)}}{2\times 2}
Square -7.
x=\frac{-\left(-7\right)±\sqrt{49-8\left(-7\right)}}{2\times 2}
Multiply -4 times 2.
x=\frac{-\left(-7\right)±\sqrt{49+56}}{2\times 2}
Multiply -8 times -7.
x=\frac{-\left(-7\right)±\sqrt{105}}{2\times 2}
Add 49 to 56.
x=\frac{7±\sqrt{105}}{2\times 2}
The opposite of -7 is 7.
x=\frac{7±\sqrt{105}}{4}
Multiply 2 times 2.
x=\frac{\sqrt{105}+7}{4}
Now solve the equation x=\frac{7±\sqrt{105}}{4} when ± is plus. Add 7 to \sqrt{105}.
x=\frac{7-\sqrt{105}}{4}
Now solve the equation x=\frac{7±\sqrt{105}}{4} when ± is minus. Subtract \sqrt{105} from 7.
2x^{2}-7x-7=2\left(x-\frac{\sqrt{105}+7}{4}\right)\left(x-\frac{7-\sqrt{105}}{4}\right)
Factor the original expression using ax^{2}+bx+c=a\left(x-x_{1}\right)\left(x-x_{2}\right). Substitute \frac{7+\sqrt{105}}{4} for x_{1} and \frac{7-\sqrt{105}}{4} for x_{2}.